THE INFLUENCE OF FAMILY COMMUNICATION PATTERNS ON ADULT CHARACTER FORMATION: A BIBLIOMETRIC STUDY - Luria Hawa, Lia (PT. Jurnal Center Indonesia Publisher, 2025)
Family communication plays a fundamental role in shaping an individual's character, particularly in adulthood. This study examines the influence of family communication patterns on adult character formation through a bibliometric analysis. Utilizing a Systematic Literature Review (SLR) and bibliometric approach, this research explores key trends, theoretical frameworks, and scholarly discussions related to family communication and character development. The study highlights the significance of open, trust-based, and emotionally supportive communication in fostering essential adult traits such as responsibility, integrity, empathy, and adaptability. Findings suggest that families with high conversation orientation cultivate individuals with stronger social skills and problem-solving abilities, whereas rigid conformity-oriented communication may hinder independent decision-making. Additionally, digital communication emerges as a growing factor influencing family dynamics. By mapping research trends and analyzing citation patterns, this study provides valuable insights into the long-term impact of family communication on adulthood and offers recommendations for future research.